Comparison of anthropometric characteristics and muscle strength of girls aged 9 to 11 years of practicing and non-practicing regular exercise - Crippa, Franciela (2013)
Childhood and adolescence are important periods for the accomplishment of healthy activities that provide a better growth of the human body. This study aimed to compare the anthropometric characteristics and muscular strength in girls aged between 9 and 11 years old that practice or do not physical exercises regularly. The data sample consisted of 40 girls, divided in two groups, 20 girls that practice physical exercises and 20 girls which do not practice it regularly. The children were evaluated through three tests of PROESD-BR, they are: lower limb strength, upper limb strength and abdominal resistance-strength; and also through anthropometric measurements: muscular mass, stature, skin folds, perimeters and diameters. For the statistical analysis, initially, the data normality and the homogeneity of the variances were verified through the tests Shapiro-Wilk and Levene. A teste t de student was done later to verify the differences among the groups. The results showed that in the anthropometric characteristics, only the fat percentage presented some difference among the groups, being more elevated in those non-practicing girls. In relation to the muscular strength tests, the practicing group showed increased levels in relation to strength. The group practicing regular exercise showed higher levels of muscle strength and a lower fat percentage when compared to non-practicing regular exercise.